Identity Politics in Islamic Views - Elly Warnisyah Harahap; Nurajidah Dalimunthe; Annisa Pratiwi Surianto (al-Afkar, Journal For Islamic Studies, 2024)
This article seeks to lift back years of efforts by religious entities to remedy conflict and help build peace. Because in today's people's lives, conflicts are much more interesting to discuss and the efforts of religious leaders to end conflicts and build peace are not too massively discussed. Identity as a political tool in Islamic teachings is permissible, but with conditions including: Not harming each other, not putting each other down or making fun of each other, not using violence (racism), distinguishing one group from another, tribe or race (ethnic fanaticism).